Communication Behaviors of County Extension Directors Post-Hurricane - Amanda D. Ali; Angela B. Lindsey; Amy M. Harder; Lisa K Lundy; Grady Roberts (Journal of Applied Communications, 2020)
In disaster crises, communication among stakeholders and response organizations are important. In Florida, the role of the County Extension Director (CED) is threefold – educational programming, leadership of a county extension program, and county office administrative responsibilities. However, their primary role in disaster emergencies is to facilitate collaborations with state and federal partners. During Hurricane Irma in 2017, UF/IFAS CEDs assisted in response efforts. However, communication efforts can become challenging in such chaotic and stressful situations. This research explored communication challenges among CEDs, clients, and statewide partners in hurricane events. Insights into the communication role of CEDs could enhance UF/IFAS Extension’s communication plan for effective information dissemination post-disaster. The Uses and Gratifications Theory guided this qualitative study. Interviews occurred with nine CEDs from various counties across Florida. Results showed CEDs used numerous communication channels to connect with clients, staff, and statewide partners, mainly for the purposes of information dissemination. The main reasons for selecting these communication channels depended on its accessibility, reliability, and whether it was a usual form of communication. Some participants were unaware of available resources which resulted in duplicate efforts. Thus, they required additional information from statewide partners. Some participants also had difficulty connecting clients with people who could assist them with insurance information and aid. As such, this study recommended a central communication system to avoid redundant efforts, strengthening relationships with disaster agencies to promote information-sharing and avoid miscommunication, and developing a list of resources and contacts for CEDs’ first engagement in disaster response.
Keywords: communication behaviors; county Extension directors; hurricane; post-disaster response; uses and gratifications